Une source nouvelle de l’Histoire de la Reine du Matin et de Soliman, Prince des Génies de Gérard de Nerval - Beylot, Robert (Aethiopica, 2008)
In his work about Solomon and the Queen of Sheba, Gérard de Nerval brings three characters together, Solomon, the Queen and Adoniram. He was interested in a French author of the XVIIIth century, Nicolas Lenglet-Dufresnoy. Nerval seems to have read in a book of the same, about Hermetism, the title of a work from Michael Maier, German alchemist of the late Renaissance, the Septimana Philosophica which consists of a philosophical dialogue between Solomon, the Queen of Sheba and Hyram, Prince of Tyre, about Nature’s aenigma. It is suggested that the French writer could have known also two other works from Michael Maier.